PERCEPTION OF THE YOUNGER GENERATION OF KARO ABOUT RAKUT SITELU - Noviani Noviani; Eka Susanti (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2025)
This research examines and analyzes the perceptions of Karo’s young generation regarding Rakut Sitelu. In the Karo people, there is a kinship system which is usually called rakut sitelu, which means triple bond. Rakut sitelu in Karo society consists of three elements, namely kalimbubu, senina, and anak beru. And of these three elements, each has its own function and role. This third element is the basis for the Karo people to create a relationship (kinship). Therefore, every Karo community, especially the young Karo generation, is obliged to know these three elements. The aim of this research is to examine and analyze the perceptions of the younger generation of Karo regarding rakut sitelu, as well as the efforts of the young generation of Karo in maintaining rakut sitelu. In this research, researchers used qualitative research, with descriptive methods. Because by using descriptive methods, researchers can explain the perceptions and efforts of the young Karo generation to understand and maintain specific sitelu rakut that occurs in Karo society, especially the young Karo generation. In accordance with the aim of this research, regarding the Karo young generation’s perception of rakut sitelu, it was found that the three elements of rakut sitelu are the foundation (basis) for the Karo people to know their position in traditional ceremonies, so that by understanding rakut sitelu, they can understand their position. The highest is owned by Kalimbubu